Kommunikationskanal för social verksamhet - Khalaf, Jean-Paul; Ulfung Arnbom, Erik (My University, 2025)
This report presents the design, implementation and evaluation of a push notification system integrated into an existing Unity-based mobile application for a youth center. An agile, sprint-driven methodology guided the work, which involved selecting Firebase Cloud Messaging (FCM) for cross-platform notification delivery, developing a Node.js/TypeScript REST API with Express and a PostgreSQL backend containerized via Docker, and creating an administrative web interface to trigger notifications. Key challenges addressed include secure token handling through FCM topics, platform-specific configuration in Unity for Android and iOS, and maintaining a reliable message history within the app. The system was validated through emulator and real-device tests (Google Play Console, Apple TestFlight) and user feedback sessions. The resulting solution offers a robust, scalable communication channel balancing technical functionality and usability.
Keywords: pushnotiser; Firebase Cloud Messaging; Unity; Android; iOS; mobilapplikation; backend; Node.js; TypeScript; PostgreSQL; Docker; användartester